The human larynx physiological and pathophysiological aspects - Munjal, Manish; Munjal, Shubham; Sadhu, Kanwarpreet; Gupta, Vidushi; Badyal, Hem Lata; Sidhu, Joginder; Sharma, Garima; Kaur, Roop Harnoor (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
In this era of minimally invasive surgical intervention s, the knowledge of the physiology and pathophysiology of the larynx is vital to the laryngologist. The conventional procedure of laryngeal surgery has been superseded by functional micro-laryngeal surgery whereby now the emphasis is not on removing the pathology but reverting the function of the larynx. The surgical intervention is at the superficial mucosal level only. The physiology and patho-physiology of the larynx needs introspection.